Bioaccessibility of phenolic compounds following in vitro large intestine fermentation of nuts for human consumption. (15th April 2018) - Rocchetti, Gabriele; Chiodelli, Giulia; Giuberti, Gianluca; Lucini, Luigi
Highlights: Different edible nuts deliver phenolic compounds to large intestine. Polyphenols degraded into low molecular weight compounds. Bioaccessibility was not negligible for alkylphenols, tyrosols and phenolic acids. Metabolomics-based profiling traces polyphenols during in vitro fermentation model. Abstract: A bioaccessibility study of polyphenols after in vitro simulated large intestine fermentation was carried out on edible nuts. Raw nuts were also analysed for total phenolic content and antioxidant potential, considering both bound and free phenolics. The highest phenolic content was found in walnuts, followed by pistachios extracts (596.9 and 410.1 mg gallic acid equivalents 100 g −1, respectively). Consistently, the total antioxidant capacity was highest in walnuts (3689.7 μM trolox equivalents 100 g −1 ) followed by peanuts and pistachios (3169.6 and 2990.1 μM trolox equivalents 100 g −1, respectively). Data showed high correlations between total phenolics and both antioxidant activities. The metabolomics-based phenolic profile depicted during in vitro fermentation showed a degradation of higher-molecular-weight phenolics over 48 hours of faecal fermentation, with a concurrent increase in low-molecular-weight compounds (hydroxybenzoic and hydroxycinnamic acids, alkylphenols, and tyrosols). Our findings indicate that nuts deliver polyphenols into the colon, with bioaccessibility values not negligible for alkylphenols, tyrosols and phenolic acids.